2008
DOI: 10.4103/0972-2327.42933
|View full text |Cite
|
Sign up to set email alerts
|

Global workspace model of consciousness and its electromagnetic correlates

Abstract: The global workspace of consciousness was proposed in its elementary framework by Baars, in 1982. Since the time of inception, there have been many speculations and modifications of this theory, but the central theme has remained the same, which refers to the global availability of information in the brain. However, the present understanding about the origin of this global workspace or its mechanism of operation is still deficient. One of the less-studied candidates for this global workspace is the electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…must take place before accurate predictions of the world can be integrated with incoming stimuli and experienced as such [124]. By integrating stored knowledge, current context, and higher cognitive functions with sensory input, there is an immense reduction in the necessity of considering large numbers of external causes for sensory events which enables quicker [127] and more accurate [128] conscious interpretation of such events [124].…”
Section: The Top-down Domination Of Perceptionmentioning
confidence: 99%
“…must take place before accurate predictions of the world can be integrated with incoming stimuli and experienced as such [124]. By integrating stored knowledge, current context, and higher cognitive functions with sensory input, there is an immense reduction in the necessity of considering large numbers of external causes for sensory events which enables quicker [127] and more accurate [128] conscious interpretation of such events [124].…”
Section: The Top-down Domination Of Perceptionmentioning
confidence: 99%
“…Frölich and Mc Cormick;Foffani, 2003). Abundant information on this dynamic research field can be found in : Fröhlich, 1968;Addey, 1993;Sedlak, 1993;Davydov, 1977;Cosic, 1997;Popp, 2005;Prakash, 2008;Funk, 2009;Cifra et al, 2010;Levin, 2012;Plankar et al, 2011;Bischoff and Del Giudice, 2013;Brizhik, 2013;Fröhlich, 2014;Muehsam, 2014;Rouleau and Dotta et al, 2014;Belyaev, 2015;Pang, 2016;Hammerschlag, 2015 andLiboff, 2017. An integral model for harmony-like resonance as an explanation for selfconsciousness was earlier proposed by Lehar, 2003Lehar, , 2012 proposing that the synchrony observed between cortical neurons is not a signal in its own right, but rather a manifestation of a larger standing wave pattern that spans the cortical region in question, and that the structure of the standing wave encodes certain aspects of the structure of the perceived object or grouping percept. Figure 4.…”
Section: Electromagnetic Aspects Of Dynamic Models Of Consciousnessmentioning
confidence: 99%
“…Magnetic fields have been shown to easily pass skin, skull and brain tissue (Murphy and Persinger, 2011, Nummenmaa et al, 2013, Bonmassar et al 2012, Babbs, 2014 and this have been related to a toroidal computing process of neural oscillations and Ca2+ pulsing, in which all collaborative effort of glia cells also plays a role (see also Pereira and Furlan, 2007;Pereira, 2017). These aspects highlight the rising interest for electromagnetic correlates in consciousness studies (Liboff, 2017;Prakash et al 2008), in which, among other mechanisms magnetic activation of slow acting voltage-gated Ca2+ channels could play a prominent role (Bonmassar et al, 2012). Interestingly mitochondria in general could play a significant role in propagation of EM field propagation (Thar and Kuhl, 2004).…”
Section: -Quantum Coherence Mediated Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the use of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI), neuroscientists attempt to identify the neuronal pathways, which produce the conscious experience. The Global Workspace Theory (GWT) is widely accepted in the scientific community to be representative of conscious and unconscious processes (Prakash et al, 2008). It is similar to the concept of working memory in that GWT proposes experience to be momentary and subjective.…”
Section: Neurological Influences Of the Environment On Healthmentioning
confidence: 99%